Enthalpy and Mechanical Relaxation of Glassy Gelatin Films - F Badii; IA Farhat (Tehran University of Medical Sciences, 2005)
Glassy materials are not thermodynamically stable and during storage below the glass transition temperature (Tg), they are subjected to the time dependent changes towards the equilibrium. These changes are known as physical ageing, which is the basic feature of glassy materials below Tg. During ageing process, physical properties such as enthalpy and volume decrease and these changes are accompanied by important changes in mechanical properties such as change to modulus, compliance and mechanical relaxation, which are of great technological importance. The aim of this study is to investigate the occurrence of the mechanical relaxation in the glassy gelatin and compare it to the enthalpy relaxation phenomenon and try to correlate the rate of mechanical relaxation to the rate of enthalpy relaxation, which is the more reliable and frequent way for studying physical ageing. The extent of enthalpy relaxation of gelatin films with different water contents of 8%, 12 and 17%, measured by differential scanning calorimetry (DSC), was found to increase with increasing the ageing time. The mechanical behaviour of the gelatin films was measured, using dynamic mechanical thermal analysis (DMTA). The mechanical behaviour of gelatin showed time and frequency-dependent changes. Storage modulus increased during isothermal ageing and gelatin became harder and stiffer at higher frequency than that at low frequency. In order to assess the rate of mechanical relaxation, the classical time-ageing time superposition was applied to the results. The rate and extent of mechanical ageing were increased at higher water contents. A good agreement was found between the rate of the enthalpy relaxation and the changes to the mechanical properties at different water contents, suggesting that DSC measurements of enthalpy relaxation, which can be more easily implemented, can be used as indicator of mechanical changes.